Funcionalização da superfície de nanopartículas magnéticas de ferritas para aplicação em filmes finos de politiofeno: fulereno - Vasconcelos, Vitória Maria Rodrigues (2020)
The investigation of the physical properties of materials due to the reduction of dimensionality has become one of the most discussed subjects in nanotechnology. In this context, the present dissertation proposes to synthesize magnetic nanoparticles of ferrites MFe 2 O 4 (M=Co, Ni or Zn) by the proteic sol-gel method and to functionalize them with ethanoic acid (acetic), in order to promote steric impediment on the surface of the nanostructures for potential application in a photoactive layer of Polymeric Solar Cells (PSC). In this perspective, the powders of the unmodified ferrite nanoparticles, that is, without adsorbed ethanoic acid, were characterized by X-Ray Diffraction (XRD), presenting a single crystallographic phase referring to the cubic spinel structure, Transmission Electron Microscopy (TEM) indicating average particle diameters of 6.5, 12 and 11 nm for the samples of CoFe 2 O 4 , NiFe 2 O 4 and ZnFe 2 O 4 , respectively, Mössbauer Spectroscopy (MS) identifying the overlapping of the sextet (ferrimagnetic ordering) and doublet (superparamagnetic phase) lines for cobalt and nickel ferrites, while the sample of zinc was shown to be paramagnetic at room temperature, Vibrating Sample Magnetometry (VSM) indicating soft ferromagnetic behavior with saturation magnetization (M s ) inferior to the respective materials bulk, Ultraviolet-Visible Spectrophotometry (UV-Vis) featuring semiconductor samples, with values of optical gap obtained were 1.37, 1.75 and 2.12 eV for cobalt, nickel and zinc ferrites, respectively, and Thermal analysis (TA) demonstrating the efficiency of the proteic sol-gel method in the synthesis of nanostructures thermally stable. The functionalized nanoparticles were characterized by Fourier Transform Infrared Spectroscopy (FTIR), presenting the vibrational modes related to the modifying agent (ethanoic acid), while the colloidal dispersions of the modified and dispersed nanostructures in ortho-dichlorobenzene were evaluated by Dynamic Light Scattering (DLS), which showed a decrease in the solvodynamic diameter (D M ) and polydispersity index (PDI) of the samples CoFe 2 O 4 and NiFe 2 O 4 modified with 30, 180 and 720 μL ethanoic acid.